Immediacy gratification in online news consumption and its relations to surveillance, orientation and elaboration of news - Omar, Bahiyah (Elsevier Ltd., 2014)
Increasing numbers of people read newspapers online.This study uses argument about reform proposed in the theory of remediation to explain the shift from traditional print to online news sources.The argument pivots around the idea that the new media improves upon the inadequacies of older media.The improvement is manifested in the striving for “immediacy” which remediation theory considers the “goal” of media.Blending the theory of remediation and the uses and gratifications approach, this study proposes the concept of “immediacy gratifications” – a process gratification obtained in news media use.The current study uses experimental research method to test the concept of immediacy gratifications in online news consumption.The study finds that online medium has no effect on immediacy gratification and that surveillance gratification seeking and orientation in the information space do have significant effects.